The pattern of femoral diaphyseal fractures in children admitted in Sarawak General Hospital. - Ahmad Hata, Rasit (Malaysian Medical Association, 2006)
Trend towards changing the face of management for pediatric femoral fractures tends to advocate operative treatment. This study was undertaken to review our current practice in the wake of recent progress in the management of pediatric femoral fractures. Fifty patients with femoral diaphyseal fracture treated in Sarawak General Hospital were reviewed retrospectively after an average follow-up of 2.6 years. There were 36 boys and 14 girls, with a mean age of 6.2 years (range five months to 14 years). Children under six years of age constituted the majority of the patients. Half of the fractures were caused by road traffic accident. Nine patients had associated injuries. The most common site of fracture was at the middle third (N=31). The treatment regimens were delayed hip spica (DHS) in 16, immediate hip spica (IHS) in 24, plate osteosynthesis (PO) in five, titanium elastic nailing (TEN) in five, and external fixation (EF) in one. The minimum hospital stay was two days, and the maximum 33 days (mean, 9.7 days). Malunion was the commonest complication. Conservative treatment is the preferred option for children under six years of age. It is cost-effective with minimal complication. The other treatment options are reserved for specific indication in older children. Diaphyseal fractures of the femur in children can be adequately managed non-operatively.